2012
DOI: 10.3354/ame01567
|View full text |Cite
|
Sign up to set email alerts
|

Infection dynamics of Amoebophryidae parasitoids on harmful dinoflagellates in a southern Chilean fjord dominated by diatoms

Abstract: Parasitoids belonging to Amoebophryidae (Marine ALVeolate Group II or MALV II) infecting dinoflagellates were investigated in Reloncaví Fjord (southern Chile) in the austral summer 2009. Of the 12 dinoflagellate species recorded during monthly sampling, Prorocentrum micans, Dinophysis acuminata, and Phalacroma rotundata were infected by Amoebophrya spp. To assess parasitoid control of host populations, the short-term dynamics of Amoebophrya spp. were followed for 21 d during a bloom of P. micans. Host mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…in other systems [11], [26], [32]. Peaks in A. fundyense cell concentrations were followed by increased infection levels and subsequently, by release of dinospores 4–5 days later.…”
Section: Discussionmentioning
confidence: 93%
“…in other systems [11], [26], [32]. Peaks in A. fundyense cell concentrations were followed by increased infection levels and subsequently, by release of dinospores 4–5 days later.…”
Section: Discussionmentioning
confidence: 93%
“…, Alves‐de‐Souza et al. ). The relationship between the mid‐Atlantic Dinophysis population and nutrients, prey, and species‐specificity between host and parasite will be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Amoebophrya infection is a widespread interspecific interaction among planktonic dinoflagellates in coastal and oceanic ecosystems around the world (Alves‐de‐Souza et al. ; Elbrächter and Schnepf ; Erard‐Le Denn et al. ; Siano et al.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated maximum level of infection (I max ) was 92.22 AE 5.43%, and the initial slope of the fitted curve (a) was 21.21 AE 1.24 (r 2 = 0.9518; P < 0.0001). oceanic ecosystems around the world (Alves- de-Souza et al 2012;Elbr€ achter and Schnepf 1998;Erard-Le Denn et al 2000;Siano et al 2011). Recent studies have revealed its enormous diversity Guillou et al 2008;Li et al 2014;Lima-Mendez et al 2015) and resulted in further investigation of its ecological role in marine ecosystems.…”
Section: Parasitoid Prevalence As a Function Of Inoculum Sizementioning
confidence: 99%